Sci Reloaded: Introducing the New Aims and Scope - Ahmad Yaman Abdin; Claus Jacob (Sci, 2024)
We are excited to share with you a crucial moment in the journey of Sci (ISSN 2413-4155) as we are announcing its new Aims and Scope [...]